Managerial Diplomacy: Strategic Leadership in Reconstructing Afghanistan’s Global Economic and Political Engagement - Karim Azizi (Penerbit Goodwood, 2025)
Purpose: This study examines how managerial diplomacy and strategic leadership shape Afghanistan’s post-conflict engagement with the global community, focusing on leadership competencies, institutional bridging between formal and traditional structures, and the effects of international aid on domestic policy autonomy. Methodology: A qualitative, stakeholder-based design was used, drawing on a structured survey administered to twenty-one Afghan governance experts between October 24 and 28, 2025, of whom twenty complete responses were retained. Respondents included NGO professionals, former government officials, policy analysts, and international diplomats. Open-ended responses across six thematic domains were analyzed using systematic text preprocessing, frequency counting, and thematic coding. Results: The analysis found that leadership legitimacy, cross-ethnic representation, and institutional hybridity dominate stakeholder narratives, while corruption and aid dependency emerged as the most cited barriers to sustainable reconstruction, each appearing in more than half of the coded concept instances. Conclusions: Effective managerial diplomacy in Afghanistan requires leaders who can simultaneously anchor legitimacy in traditional structures, coordinate fragmented donor relationships, and preserve strategic sovereignty over domestic decisionmaking. Limitation: The sample size and single-country focus limit generalizability. Contributions: The study extends strategic leadership and diplomatic studies literature into a non-Western, post-conflict governance context and proposes a conceptual model linking leadership, state capacity, and diplomatic outcomes.